THE ROLE OF METABOLIC FACTORS IN THE DEVELOPMENT OF RENAL DYSFUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION - Sultanov , S.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Arterial hypertension (AH) is a common and serious disease characterized by persistently high blood pressure, which has a significant negative impact not only on the cardiovascular system, but also on respiratory, nervous and renal function. High blood pressure is associated with serious damage to various organs, including the kidneys, over a long period of time. In particular, nephropathy, which occurs as a result of impaired kidney function due to hypertension, negatively affects the quality of life of many patients and leads to aggravation of the disease. Kidney damage caused by AH leads to chronic renal failure, increasing mortality and disability among the population. Aim. The effect of arterial hypertension on the development of renal dysfunction. Materials and Methods. The study examined the impact of disease processes on dysfunction in hypertensive patients, their pathophysiological mechanisms, and clinical significance. A group of 80 patients with renal dysfunction, with and without arterial hypertension were included in the study. Results: According to the results of the study, when comparing groups 1 and 2, a significantly higher urinary microalbuminuria was observed in group 2 compared to group 1, respectively (30.27±2.47-91.56±18.11). The results obtained showed that metabolic factors can negatively affect the course and development of the disease in patients with arterial hypertension and develop kidney disease, causing severe complications. Conclusion: In patients with arterial hypertension, the process of reloading is early loading. Their help and treatment strategies can be improved. All medical diseases must be individualized, because each patient's condition is unique and specific.